Odpowiedzi

2010-01-04T15:51:39+01:00
A)(2a-1)²=(2a+1)(2a-1)
4a²-4a+1=4a²-1
-4a=-2 /:(-4)
a=½

b)(3x+2)(3x-2)-9(x+1)²=-22
9x²-4-9(x²+2x+1)=-22
9x²-4-9x²-18x-9=-22
-18x=-9 /:(-18)
x=½
2010-01-04T16:09:13+01:00
Rozwiąż równanie.
a)(2a-1)²=(2a+1)(2a-1)
4a²-4a=1=4a²-1
-4a=-2 /:(-4)
a=1/2

b)(3x+2)(3x-2)-9(x+1)²=-22
9x²-4-9(x²+2x+1)+22=0
9x²-4-9x²-18x-9+22=0
-18x=-22+13
-18x=-9 /:(-18)
x=1/2
2010-01-04T16:14:20+01:00
A)
(2a-1)²=(2a+1)(2a-1)
(2a)²-2*2a*1+1²=(2a)²-1²
4a²-4a+1=4a²-1
-4a=-2
a=1/2

b)
(3x+2)(3x-2)-9(x+1)²=-22
(9x²-4)-9(x²+2x+1²)=-22
9x²-4-9x²-18x-9=-22
-4-18x-9=-22
-18x=-9
x=1/2